Teacher Reflection on the Implementation of the Independent Curriculum in Elementary Schools - Syamsur Rizal (Formad English Foundation NTB Jakarta, 2025)
The implementation of the Merdeka Curriculum in elementary schools demands a paradigm shift in learning that is more contextual, differentiated, and oriented toward strengthening the Profile of Pancasila Students. However, in reality, many teachers still face challenges in understanding and effectively applying this curriculum. This study aims to reflect on teachers’ experiences in implementing the Merdeka Curriculum at the elementary school level. This research employed a qualitative approach with a case study design conducted in four elementary schools in Wanasaba District over a period of three months, from January to March 2025. Data collection techniques included semi-structured interviews, participatory observation, and documentation involving 25 informants consisting of principals, teachers, and students. The results of the study indicate that most teachers have understood the basic concepts of the Merdeka Curriculum but face difficulties in its practical implementation, such as designing differentiated instruction, conducting formative assessments, and building a culture of reflection. Structural support from schools and other stakeholders is also still limited. The lack of ongoing training and supporting facilities is a significant obstacle in the adaptation process to this new curriculum. In conclusion, teachers' reflections reveal a gap between theoretical understanding and the practical application of the Merdeka Curriculum. Therefore, systematic efforts are needed to enhance teacher competence through training, mentoring, and strengthening collaborative learning communities to support the successful implementation of the curriculum in elementary schools.